2019
DOI: 10.17509/jsl.v2i2.16204
|View full text |Cite
|
Sign up to set email alerts
|

Development of Smart Content Model-based Augmented Reality to Support Smart Learning

Abstract: Augmented Reality (AR) is an optical technology that combines virtual objects or worlds into real worlds like in real time and increases user perceptions and interactions with the real world. Information conveyed by virtual objects helps users carry out activities (tasks) in the real world. The convenience offered makes AR technology can be used for various fields, including education, such as the development of materials or learning media. Augmented reality in its development is more comfortable, cheaper, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
7
0
3
Order By: Relevance
“…Further review on the selected articles found that AR learning influenced students' motivation in learning mathematics. This can be discovered in a recent study by Fatimah et al (2019) stating that mathematical material which executed AR-based technology could increase students' motivation and challenges. Similarly, AR-based technology promotes students' motivation which can enhance them to acquire mathematics knowledge (del Cerro Velázquez & Morales Méndez, 2021;Elsayed & Al-Najrani, 2021), increase learning motivation by using interactive technology (Lainufar et al, 2021), reduce students' level of mathematics anxiety (Saha et al, 2020) and aid students with high self-efficacy in learning mathematics by encouraging them to employ deep techniques (Cai et al, 2018).…”
Section: The Learning Outcomes In Implementation Of Armentioning
confidence: 95%
See 2 more Smart Citations
“…Further review on the selected articles found that AR learning influenced students' motivation in learning mathematics. This can be discovered in a recent study by Fatimah et al (2019) stating that mathematical material which executed AR-based technology could increase students' motivation and challenges. Similarly, AR-based technology promotes students' motivation which can enhance them to acquire mathematics knowledge (del Cerro Velázquez & Morales Méndez, 2021;Elsayed & Al-Najrani, 2021), increase learning motivation by using interactive technology (Lainufar et al, 2021), reduce students' level of mathematics anxiety (Saha et al, 2020) and aid students with high self-efficacy in learning mathematics by encouraging them to employ deep techniques (Cai et al, 2018).…”
Section: The Learning Outcomes In Implementation Of Armentioning
confidence: 95%
“…The results of the analysis based on conceptual knowledge found that AR-based learning media can help students understand integer material, solve integer problems in daily life, utilize mathematical concepts of algorithm and can contribute to increasing students' critical thinking skills (Medina Herrera et al, 2019;Suryanti et al, 2020). Fatimah et al (2019) advocated that multimediabased AR in mathematical materials can facilitate students' understanding in learning mathematics concepts. In addition, the application of AR technology aids students in the mathematical modelling process, generate mathematical function particularly at the stage of comprehending real-world situations (Cahyono et al, 2020;del Cerro Velázquez & Morales Méndez, 2021).…”
Section: The Learning Outcomes In Implementation Of Armentioning
confidence: 99%
See 1 more Smart Citation
“…Media pembelajaran yang berkembang di bidang IPTEK tentunya akan menunjang kemajuan dan perubahan positif dalam bidang pendidikan. Dengan media pembelajaran yang menarik seperti tayangan atau tampilan bergerak akan membuat peserta didik lebih mudah mengingat dan menyerap materi (Fatimah et al, 2019). Salah satu contoh media pembelajaran adalah buku ajar yang digunakan dalam proses belajar mengajar.…”
Section: Pendahuluanunclassified
“…Augmented Reality dapat meningkatkan persepsi dan interaksi pengguna dengan yang sebenarnya secara virtual. Dengan teknologi AR, maka proses pembelajaran akan lebih menyenangkan dan dinamis (Fatimah et al, 2019). Berdasarkan latar belakang masalah di SMK Negeri Kota Malang Progam Keahlian Multimedia membuat peneliti termotivasi untuk membuat media pembelajaran buku ajar yang dibantu dengan teknologi Augmented Reality dengan judul "Pengembangan Media Pembelajaran berbasis Augmented Reality pada Mata Pelejaran Teknik Animasi 2D 3D Kompetensi Keahlian Multimedia Sekolah Menengah Kejuruan".…”
Section: Pendahuluanunclassified